CONVERSATIONAL IMPLICATURES OF INDONESIA LAWYERS CLUB PROGRAM ON TV ONE - Lubis, Indah Sari (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2015)
This study deals with the conversational implicatures on Indonesia Lawyers Club program on TV One. The objectives of the study are (1) to observe the types of maxim violation potentially cause conversational implicature, (2) to ascertain the maxim violation that dominantly causes conversation implicatures, (3) to give the reasons of the dominant type of violation that causes conversational that causes conversational implicatures on Indonesia Lawyers Club program by using Gricean Theory of Cooperative Principle. The study is conducted by qualitative content analysis. The findings of the study are, (1) there are four types of maxim violations as maxim of quantity, maxim of quality, maxim of manner, and maxim of relevance, (2) the dominant type of maxim violation appeared is maxim quantity and (3) the reasons of the dominant type deal with, to show up pain and core of the problem to the audience, to save one face, to defend certain group and blame the government.Keywords: conversational implicature, cooperative principle, maxim violation, Indonesia Lawyers Club